Translational Use of a Standardized Full Human Skin Organ Culture Model in Autoimmune Blistering Diseases. Issue 1 (8th March 2019) - Burmester, Imke A. K.; Emtenani, Shirin; Johns, Jan‐Gerrit; Ludwig, Ralf J.; Hammers, Christoph M.; Hundt, Jennifer E.
Abstract: The full human skin organ culture (HSOC) model is a standardized test system for evaluating pharmacological substances on human skin in vitro . The acantholysis associated with pemphigus vulgaris (PV), a severe and potentially life‐threatening autoimmune skin blistering disease, can be induced in HSOC by injecting a bi‐specific anti‐desmoglein (dsg) 1 and 3 single‐chain antibody variable fragment (scFv). Compared to cell culture experiments (e.g., induction of dsg3‐internalization or keratinocyte dissociation using HaCaT cells or normal human epidermal keratinocytes) the HSOC model is more sophisticated and physiologically relevant. In this model, all three layers of the human skin are present, all cells are sustained in their physiological niche and orientation, and the cell‐cell‐contacts remain intact. Here we describe a protocol for HSOC, an ex vivo model of human skin, that has proved to be well‐established and informative in our laboratory. © 2019 by John Wiley & Sons, Inc.